2021
DOI: 10.3389/fmed.2021.702066
|View full text |Cite
|
Sign up to set email alerts
|

Original Hosts, Clinical Features, Transmission Routes, and Vaccine Development for Coronavirus Disease (COVID-19)

Abstract: The pandemic of coronavirus disease 2019 (COVID-19), which is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has led to public concern worldwide. Although a variety of hypotheses about the hosts of SARS-CoV-2 have been proposed, an exact conclusion has not yet been reached. Initial clinical manifestations associated with COVID-19 are similar to those of other acute respiratory infections, leading to misdiagnoses and resulting in the outbreak at the early stage. SARS-CoV-2 is predominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 192 publications
(220 reference statements)
0
10
0
Order By: Relevance
“…Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), the etiologic agent of coronavirus disease 2019 (COVID‐19), is mainly transmitted by respiratory droplets and direct contact with respiratory droplets between humans, and may be transmitted by aerosols when exposed to high concentration of SARS‐CoV‐2 contaminated aerosols for a long time in a relatively closed environment. 1 , 2 Meanwhile, some studies have found that SARS‐CoV‐2 also transmitted by fomite contact, a more complex and hidden transmission route, may introduce SARS‐CoV‐2 into the low prevalence countries and regions. 3 , 4 , 5 …”
Section: Introductionmentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), the etiologic agent of coronavirus disease 2019 (COVID‐19), is mainly transmitted by respiratory droplets and direct contact with respiratory droplets between humans, and may be transmitted by aerosols when exposed to high concentration of SARS‐CoV‐2 contaminated aerosols for a long time in a relatively closed environment. 1 , 2 Meanwhile, some studies have found that SARS‐CoV‐2 also transmitted by fomite contact, a more complex and hidden transmission route, may introduce SARS‐CoV‐2 into the low prevalence countries and regions. 3 , 4 , 5 …”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 predominantly spreads via the respiratory tract and through close contact. The main transmission route is droplet transmission, as the viruses from the infected respiratory tract can directly infect mucous membranes of people within 2m proximity ( Wu et al., 2021 ). Some evidence of airborne and fecal-to-oral transmission, but clinical cases of these mechanisms have not been reported ( Wu et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main transmission route is droplet transmission, as the viruses from the infected respiratory tract can directly infect mucous membranes of people within 2m proximity ( Wu et al., 2021 ). Some evidence of airborne and fecal-to-oral transmission, but clinical cases of these mechanisms have not been reported ( Wu et al., 2021 ). Other routes such as sexual, vertical transmission, and breastfeeding are the possible concerns of COVID-19 transmission ( Wu et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SARS-CoV-2 infection is worldwide; the virus mutates fast, speeding the spreading of the infection and subsequent disease (Covid-19) due to numerous consecutive emerging variants, each more infectious than the previous one. Efficient vaccines have been made available against the first viral strains within an amazingly short period of time [1] . Despite this tremendous achievement, too few people can get full vaccination schedule to successfully stop the virus progression, and many places in the world are currently struggling to fight both the virus transmission and the disease especially in the most vulnerable populations [2] .…”
mentioning
confidence: 99%